Attributes of Primary Health Care in Child Care in São Paulo/SP (Research, Society and Development, 2023)
The objective was to evaluate the attributes of Primary Health Care (PHC) in the care of children in Basic Health Units (UBS). Cross-sectional study with a quantitative approach, carried out in 13 UBS in the city of São Paulo/SP, in the year 2021. The PCATool-Brasil instrument for children was used to assess PHC attributes. The scores of each attribute were evaluated separately and also the general and essential scores. The sample was characterized from the mean and standard deviation, minimum and maximum, median and quartiles, for quantitative variables, and by absolute and relative frequencies for qualitative variables. 242 children participated, with a mean age of 3.33 years and essential scores with values of (6.41) and general (6.20) respectively. The results of the scores were low and, therefore, in need of improvements in PHC services. The results of the essential and general scores presented as low and, therefore, in need of improvements in the PHC services show the constant search for their evaluations, aiming at a qualified management that brings greater resolution to the PHC.